A deadline-based algorithm for dynamic task scheduling with precedence constraints - Chuprat, Suriayati; Salleh, Shaharuddin (ACTA Press, 2007)
This paper presents a new deadline-based algorithm for dynamic task scheduling on multiprocessor real-time systems. The proposed algorithm was built based on the well-known dynamic scheduling algorithm the Earliest Deadline First (EDF). We extend the EDF algorithm in three significant criterions: (1) The original EDF deals with set of periodic task. (2) It schedules only independent tasks. (3) It works best in the single processor system. Our contribution in this study is a creation of a new variation of EDF called EDF-pc that able to schedule set of non-periodic tasks. It also deals with tasks that may or may not have precedence constraints and it produced acceptable results in the multiprocessor systems.